2009
DOI: 10.1007/s11274-009-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of diosgenin from yellow ginger (Dioscorea zingiberensis C. H. Wright) saponins by commercial cellulase

Abstract: A commercial cellulase was first assessed to be effective in hydrolyzing glycosyl at the C-3 and C-26 positions in steroidal saponins from yellow ginger (Dioscorea zingiberensis C. H. Wright) to diosgenin, a very important chemical in the pharmaceutical industry. The effect of different parameters on enzyme hydrolysis was further investigated by systematically varying them. The highest yield was achieved when the hydrolysis ran at 55°C and pH 5.0 with an enzyme to substrate ratio of 15 × 10(3) U/g. The biotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The rhizomes of D. zingiberensis have a high content of diosgenin, which is an important precursor of semi-synthetic steroidal drugs in the pharmaceutical industry [13]. In our previous study, water-extracted mycelial polysaccharide (WPS), exopolysaccharide (EPS), and sodium hydroxide-extracted mycelial polysaccharide (SPS) of F. oxysporum Dzf17 all showed enhancing effects on diosgenin production in D. zingiberensis cell cultures [10].…”
Section: Introductionmentioning
confidence: 99%
“…The rhizomes of D. zingiberensis have a high content of diosgenin, which is an important precursor of semi-synthetic steroidal drugs in the pharmaceutical industry [13]. In our previous study, water-extracted mycelial polysaccharide (WPS), exopolysaccharide (EPS), and sodium hydroxide-extracted mycelial polysaccharide (SPS) of F. oxysporum Dzf17 all showed enhancing effects on diosgenin production in D. zingiberensis cell cultures [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the standards method, a large quantity of saponins standards need to be bought, which incurs large economic costs and necessitates tedious calculations. Studies on steroid saponins of DZW revealed that there are 11 steroid saponins in the rhizomes [22,23]. Among these saponins, zingiberensis newsaponin, deltonin, diosgenintriglucoside, diosgenin-diglucoside and trillin are the predominant ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…After extraction, pure products obtained are frequently isolated and then separated from the raw extract by column chromatography. Lin & Yang (2008) determined the quantity of diosgenin in plants of Dioscorea pseudojaponica Yamamoto using high-pressure liquid chromatography (HPLC), but gas chromatography-mass spectrometry (GC-MS) has been an effective technique for quantifying several steroidal sapogenins in Trigonella foenumgraecum and Dioscorea zingiberensis (Taylor et al, 1997;Kaufmann et al, 2007;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%